1988
DOI: 10.1143/jjap.27.l655
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity of Ba2Y(Cu, Ti)3Oy Oxide

Abstract: Samples of Ba2Y(Cu, Ti)3O y oxide were synthesized and the effect of substituting Cu with Ti was studied. In the Ba2Y(Cu3-x Ti x )O y (0≦x≦0.9), specimens were obtained which indicated a T c of over 80 K. In the composition BaαYCuβTi0.6O y (1.9≦α≦2.3, 2.3≦β≦3.5), some (Cu Ti)-rich samples indicated a T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…It was found that the increasing content of TiO 2 from 1% to 5% in a flame-quench-melt-grown (FQMG) YBa 2 Cu 3 O 7−δ bulk caused a decrease of superconducting transition temperature, while in the range from 7 to 10 wt.% T c slightly recovered again (Yanmaz et al, 2002). In the YBa 2 (Cu 3-x Ti x )O y specimens, T c of about 80 K was observed for 0≤x≤0.9 (Okura et al, 1988). (Venkataramani et al, 1988).…”
Section: Flux Pinning In Neg-123 Due To Tio 2 Nanoparticlesmentioning
confidence: 98%
“…It was found that the increasing content of TiO 2 from 1% to 5% in a flame-quench-melt-grown (FQMG) YBa 2 Cu 3 O 7−δ bulk caused a decrease of superconducting transition temperature, while in the range from 7 to 10 wt.% T c slightly recovered again (Yanmaz et al, 2002). In the YBa 2 (Cu 3-x Ti x )O y specimens, T c of about 80 K was observed for 0≤x≤0.9 (Okura et al, 1988). (Venkataramani et al, 1988).…”
Section: Flux Pinning In Neg-123 Due To Tio 2 Nanoparticlesmentioning
confidence: 98%